Pengaruh Ekspor dan Impor terhadap Nilai Kurs dalam Sektor Perdagangan - Permadi, Rangga Arya; Ramadhania, Fairuz Lathfiah; Asiah, Nur; Rahmah, Fitria (Jurnal Ekonomi-Qu, 2024)
The importance of the trade sector in a region’s economy highlights its significant influence on progress and growth, both internally and externally. Therefore, this research aims to analyze the impact of interest rates, exports and imports on exchange rates in the trade sector. The method applied is a quantitative method, using descriptive analysis and multiple linear regression analysis. Thedatacollected for this research comes from secondary data. The research result show that interest rates, export and imports have a significant influence on changes in exchange rate values. The research results show that there is a partial or simultaneous connection and influence between exports and imports on the exchange rate in the period January 2019 – June 2021.